Observations of [OI]63 μm line emission in main-sequence galaxies at z ∼ 1.5. Issue 2 (19th September 2020) - Wagg, J; Aravena, M; Brisbin, D; Valtchanov, I; Carilli, C; Daddi, E; Dannerbauer, H; Decarli, R; Díaz-Santos, T; Riechers, D; Sargent, M; Walter, F
ABSTRACT: We present Herschel –PACS spectroscopy of four main-sequence star-forming galaxies at z ∼ 1.5. We detect [OI]63  μ m line emission in BzK-21000 at z  = 1.5213, and measure a line luminosity, $L_{\rm [O\, {\small I}]63\, \mu m} = (3.9\pm 0.7)\times 10^9$  L⊙ . Our PDR modelling of the interstellar medium in BzK-21000 suggests a UV radiation field strength, G ∼ 320 G 0, and gas density, n ∼ 1800 cm −3, consistent with previous LVG modelling of the molecular CO line excitation. The other three targets in our sample are individually undetected in these data, and we perform a spectral stacking analysis which yields a detection of their average emission and an [O i ]63  μ m line luminosity, $L_{\rm [O\, {\small I}]63\, \mu m} = (1.1\pm 0.2)\times 10^9$  L⊙ . We find that the implied luminosity ratio, $L_{\rm [O\, {\small I}]63\, \mu m}/L_{\rm IR}$, of the undetected BzK-selected star-forming galaxies broadly agrees with that of low-redshift star-forming galaxies, while BzK-21000 has a similar ratio to that of a dusty star-forming galaxy at z ∼ 6. The high [O i ]63  μ m line luminosities observed in BzK-21000 and the z ∼ 1−3 dusty and sub-mm luminous star-forming galaxies may be associated with extended reservoirs of low density, cool neutral gas.